Essence of grammar according to modern linguistics and Afghan linguists’ perspectives - Hakimi, Matiullah (International Journal of Innovative Research and Scientific Studies, 2021)
The paper explored views in modern linguistic theories and Afghan linguist perspectives about essence of grammar, its original source, its function in language use and the relationship between mental rules and their description in grammar books. The data were collected from theoretical linguistics, grammar books and 10 Afghan professors who teach linguistics and Persian-Dari grammar in Kabul University via a questionnaire. MS excel was used to analyze the data. The results show the term Grammar refers to a set of constructional rules of a language located in speakers’ minds. It is unconscious knowledge which enables speakers of a language to produce and understand its utterances. These mental rules govern composition of phonemes, morphemes, words, phrases, clauses and sentences. Grammar books are like maps of original grammar which has mental essence and describe it. Children learn their native language from elders and their coeval speakers. Second language learners, can learn a foreign language through social interaction and grammar books. Compiling grammatical rules of a language introduces word formation techniques to expand its lexicon, help speakers to know more about their language capacities and possibilities. Grammar books aim to facilitate learning formal language, description of constructional rules, language learning for foreigners and provide correct writing guidelines. The research prescribes grammar teachers to use grammar as means of enrichment of formal language, as it can better function to do its scientific mission.